Approaching new production technologies A standard for how Volvo Trucks should identify, evaluate and implement new production technologies in the Tuve plant - Wirén, August Irhede; Ekman, Carin (My University, 2018)
Technology is advancing faster than ever before. The risk of not keeping up with ever changing production technology has never been more tangible. Not continually updating the production system at a manufacturing company can result in disadvantages in production performance in relation to competing companies. Volvo Trucks is not exempt from the reality of continuous technological advancement and with that the threat of falling behind. Although Volvo Trucks Tuve has a sufficiently effective production system (i.e. they are competitive), some areas suggest the lack of a standard for how to identify, evaluate and implement new production technologies in the production system. By introducing an effective standard for how to continually update and advance the production system in Tuve, Volvo Trucks can expect improvements in performance areas such as productivity, quality and flexibility and ultimately become a more competitive manufacturing company. Hence, the purpose of the thesis is to identify how new production technologies can be effectively identified, evaluated, and implemented in the production system at Volvo Trucks in Tuve. The purpose was fulfilled by conducting a thorough literature review as well as multiple case study comprising four cases of recent introductions of new technology at Volvo Trucks. The project was performed as a qualitative study, with semi structured interviews as the main data collection method. The thesis concluded that Volvo Trucks primary problem is that they don’t have a standardized approach that is continuously improved upon, resulting in limited learning and unwanted variation in the process of introducing new production technologies. A standard was created in order to remedy this problem. The standard was intended to be an overview of all important aspects to consider when approaching new process technology in general but is especially aimed at addressing Volvo Truck’s specific problems. The standard should be considered as a basis for further development and perhaps a more concrete and streamlined standard. Nevertheless, the standard is structured in a step by step manner for ease of use and Volvo Trucks can expect a more effective approach towards new production technologies by utilizing it.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Other industrial engineering and economics